Determinants of Muslim Tourist Satisfaction in a Muslim Majority Country: A Structural Equation Modeling Approach - Rana, Dr. Md. Sohel (International Journal of Applied Management and Business, 2025)
Muslim tourism represents a sizable segment of the global travel industry, mainly in Muslim-majority nations. Despite its developing significance, there is constrained research on the factors that impact Muslim tourist satisfaction in such contexts. Addressing this gap, this study investigates the determinants of Muslim tourist satisfaction by reading five key variables: halal food and beverages, destination image, religious motivation, prayer facilities, and service quality. Utilizing a quantitative technique, the study employed the Smart-PLS technique to analyze data collected from Muslim travelers. The results reveal that destination image, prayer facilities, and service quality have a widespread impact on Muslim tourist satisfaction. Nevertheless, halal foods and beverages and religious motivation no longer showed statistically significant results. These findings highlight the important influence of destination image, prayer facilities, and service quality concerning Muslim tourist experiences. The paper can contribute to the current literature by providing empirical evidence of determinants of Muslim tourist satisfaction in Muslim-majority countries and highlighting the importance of stakeholders’ awareness of how these factors need to be addressed. Practical aspects include the enhancement of targeted policies and projects for enhancing destination attractiveness, encouraging high-quality service provision, and an adequate number of places of worship to meet the demand of Muslim visitors. Future studies can also investigate the cultural and demographic influences on satisfaction in an analogous way to gain a deeper understanding.